Belief, trust, and relationality: a Simmelian approach for the study of faith. Issue 2 (3rd April 2017) - Montemaggi, Francesca E. S.
ABSTRACT: Religion has been conceptualised as personal belief in the transcendent. Anthropologists of religion have critiqued such a construct for decades for being based on a Christian Protestant model and one that reflected subsequently modern rationalist Western culture. This construct has increasingly been shown to fail to account for the religiosity of contemporary Christians. Drawing on the sociology of Georg Simmel and based on ethnographic research in a Christian evangelical church, the article proposes a reconceptualisation of religious belief that is experiential and relational. Evangelicals in this case study show that propositional belief plays increasingly a secondary role to belief intended as trust in God and forming a relationship with God and others. Relationships mediate personal religious experience and are shown to be essential to the conversion process, the life of faith, and Christian identity. The study thus bridges the separation between theoretical and empirical works by operationalising Simmel's sociology.